FRI0251 Comparison of lipid profile including high molecular weight adiponectin (HMW-AN) after treatment with three different biologics in the patients with bio-naïve rheumatoid arthritis (RA). (23rd January 2014) - Saito, K.; Hanami, K.; Hirata, S.; Kubo, S.; Nawata, M.; Yamaoka, K.; Nakayamada, S.; Nakano, K.; Tanaka, Y.
Abstract : Background: Three different mode of action of biologics (adalimumab, tocilizumab and abatacept) have been shown to provide clinical benefits in the patients (pts) who did not adequately respond to methotrexate (MTX-IR) in RA. In several studies including our report, moderate increase in cholesterol and HMW-AN, which is an anti-atherogenic adipocytokine, after treatment with TNF inhibitors has been reported 1 ) . However, there was no report in terms of comparison of effect of biologics on lipid profile. Objectives: The aim of this study is to compare the effect of TNF inhibitor (adalimumab), IL-6 inhibitor (tocilizumab) and abatacept on lipid metabolism, especially on AN, in MTX-IR, bio-naïve RA patients. Methods: From the cohort of about 1, 700 patients who received biologics in our institute, we evaluate the effect of MTX alone (52) or first line use of adalimumab (76), tocilizumab (27), abatacept (34) on lipid profile in MTX-IR pts whose LDL, HDL-C and AN at a series of 0, 24, 52wks were available. In order to remove the effect of prior biologics, corticosteroids (CS) and lipid-lowering agents, the pts who had received those drugs were excluded. Results: The baseline characteristics of the 189 pts; average of age was 58.4 and disease duration was 74.5 months and there was no significant difference among 4 groups. The disease activity decreased dramatically in each group as shown in Table (0 vs 24, 52wks, * p<0.05, ** p<0.01). Three biologics but not MTX alone increased LDL, HDL-C and HMW-AN at24 and kept the titer at 52 wks. There was no significant difference among biologics groups regarding the changes of lipid after the treatment. In addition, atherogenic index was not changed despite of increase of LDL-C. Baseline and changes of HMW-AN were not associated with type of biologics as well as disease activity. Conclusions: Our data suggest inhibition of TNF, IL-6 and T cell activation increase both LDL and HDL-C at the same degree without change in atherogenic index. Furthermore these biologics might have preventive effect on the progression of arteriosclerosis by an increase of HMW-AN. MTX alone decrease disease activity as biologics do, but do not increase AN. Our data imply us that action of the biologics for lipid metabolism could be independent on inflammation in synovitis. In this study we excluded pts with CS, lipid-lowering agents and prior biologics. However, precise mechanism of these biologics on AN remained unclear, this is the first report regarding comparison of lipid profile in the patients treated with different biologics in RA. References: Nishida K, Okada Y, Nawata M, Saito K, Tanaka Y. Endocr J. 2008 Disclosure of Interest : K. Saito Speakers bureau: Bristol-Myers Squibb, MSD K.K., Chugai Pharma Co., Ltd., Mitsubishi-Tanabe Pharma Co., Ltd., Abbott Japan Co., Ltd., Eisai Co., Ltd., K. Hanami: None Declared, S. Hirata: None Declared, S. Kubo: None Declared, M. Nawata: None Declared, K. Yamaoka: None Declared, S. Nakayamada: None Declared, K. Nakano: None Declared, Y. Tanaka Grant/research support from: Bristol-Myers Squibb, MSD K.K., Chugai Pharma Co., Ltd., Mitsubishi-Tanabe Pharma Co., Ltd., Astellas Pharma Inc., Abbott Japan Co., Ltd., Eisai Co., Ltd. and Janssen Pharmaceutical K.K., Speakers bureau: Mitsubishi-Tanabe Pharma Co., Ltd., Abbott Japan Co., Ltd., Eisai Co., Ltd., Chugai Pharma Co., Ltd., Janssen Pharma K.K., Santen Pharma Co., Ltd., Pfizer Japan Inc., Astellas Pharma Inc., Daiichi-Sankyo Co., Ltd., GlaxoSmithKline K.K., Astra-Zeneca, Otsuka Pharma Co., Ltd., Actelion Pharma Japan Ltd., Eli Lilly Japan K.K., Nippon Kayaku Co., Ltd., UCB Japan Co., Ltd., Quintiles Transnational Japan Co. Ltd., Ono Pharma Co., Ltd.